Monitoring Suhu Box Panel dan Voltase Pengisian Baterai pada Base Transceiver Station Berbasis IoT - Andy Ariyanto; Nurchim Nurchim; Dwi Hartanti (G-Tech: Jurnal Teknologi Terapan, 2024)
Started with the frequent running out of backup battery power at the Wifi Base Transceiver Station (BTS) due to frequent power outages in the BTS area and the high temperature inside the panel box. This problem can be overcome by research into a panel box temperature monitoring system and battery charging voltage in IoT-based BTS. The system development used is a prototype method, which can overcome problems between users and researchers. Researchers used ESP32 Wrover as a microcontroller, voltage divider as a voltage sensor and DHT11 as a temperature sensor. If the charging voltage is less than 11 volts and/or the voltage is more than 15 volts then the ESP32 Wrover will send a Telegram message to the user and if the temperature read by the DHT11 sensor is more than 40 degrees Celsius then the system will turn on the relay connected to the cooling fan, the fan will be turned off when the temperature drops to 30 degrees Celsius.